Drying and Milling Cost Functions of Paddy: Empirical Estimates for Government Processing Complexes in Malaysia - Ghaffar, Roslan A.; Chew , T. A; Hassan, Azman (1988)
In this paper, the statistical cost function approach was used to model the drying and milling cost for government paddy/rice processing complexes in Malaysia. The quadratic and inverse cost [unctions were estimated. The results suggest that there exists cost economies at relatively high output levels for both the drying and milling operations. Examination of output data indicates that a large number of government paddy mills operate at low outputs, with cost economies unexploited.